Indications, Feasibility, and Safety of TST STARR Plus Stapler for Degree III Hemorrhoids: A Retrospective Study of 125 Hemorrhoids Patients - Wei, Jun; Ding, Xufeng; Jiang, Jie; Ji, Lijiang; Huang, Hua (Frontiers in Surgery, 2022)
Background: Stapler hemorrhoidopexy (SH) has been widely accepted for hemorrhoids patients because of its low postoperative pain, but it is also associated with a high recurrence rate. The recurrence might be due to failure to completely remove the prolapsed tissue or insufficient removal capacity of the instruments. Removing more prolapsed tissue to reduce the recurrence is believed to benefit more severe prolapsed hemorrhoids patients. Methods: We evaluated the short- and long-term safety and efficacy in 125 hemorrhoids patients who underwent SH in 2013-2015. Eighty patients had prolapsed tissue less than half of the circular anal dilator (CAD) and underwent a procedure for prolapsing hemorrhoids (PPH), while the remaining 45 patients with hemorrhoid prolapse greater than half of the CAD were treated with a tissue selection therapy stapler stapled transanal rectal resection plus (TST STARR+). Results: There were no significant differences between the two groups in terms of operative time, hospitalization time, overall satisfaction or complications. At follow-up of up to 4 years after surgery, there was no significant difference in recurrence rates between TST STARR+ group and PPH group (5.2% vs. 4.7%, p<0.05). The mean width and volume of the resected tissues were significantly larger in the TST STARR+ group than in the PPH group (4.8 vs. 2.9 cm, 10.2 vs. 4.4 cm3, P<0.05). Conclusion: The TST STARR+ procedure can remove more hemorrhoidal tissue than PPH and it is better suited for patients with severe annular prolapsed hemorrhoids greater than half of the CAD. It has the advantages of convenient to operate, rapid recovery, fewer complications, and long-term satisfactory results.